Control of cardiac metabolism and efficiency - Murray, A; Andrew James Murray (2003)
For many years high levels of plasma non-esterified fatty acids (NEFAs) have been associated with a decreased cardiac energy stores, though the mechanism for this has been elusive. The aim of this thesis was to investigate the possible detrimental effects of the elevated plasma NEFA levels that have been reported in heart failure. In the chronically ligated rat heart, a model of heart failure post-myocardial infarction, levels of UCP2 and UCP3 were increased, correlating with increased plasma NEFAs, and were associated with increased mitochondrial uncoupling. The cardiac mitochondria isolated from these rats were less abundant and had a reduced maximal respiratory capacity, possibly due to mitochondrial DNA damage mediated by reactive oxygen species. Patients with heart failure have insulin resistance, here it was found that the chronically ligated heart had reduced uptake of D[2-3H] glucose after stimulation with insulin. This was associated with decreased cardiac levels of the insulin-responsive glucose transporter, GLUT4, the levels of which correlated negatively with plasma NEFAs. D[2-3H] glucose uptake was also reduced during cardiac ischaemia, leading to greater loss of ATP and lower contractile recovery upon reperfusion. In human heart, levels of UCP2 and UCP3 correlated positively with plasma NEFA concentrations, and may explain the decrease in phosphocreatine that is reported in heart failure patients. Also, levels of GLUT4 in heart and skeletal muscle correlated negatively with plasma NEFA concentrations, and could result in myocardial insulin resistance in heart failure patients. In conclusion, increased levels of circulating NEFAs in rats post-myocardial infarction, increased cardiac levels of UCP2 and UCP3, which were associated with increased mitochondrial uncoupling, and decreased cardiac levels of GLUT4, which were associated with insulin resistance and impaired energy metabolism. Similarly, in patients, high levels of NEFAs were associated with increased cardiac UCP levels and decreased GLUT4 levels in heart and skeletal muscle. This could explain the reduction in myocardial energy stores in heart failure patients which have high plasma NEFA levels.